1996
DOI: 10.1192/bjp.168.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Social Phobia in General Health Care: An Unrecognised Undertreated Disabling Disorder

Abstract: SP appears to be a true and frequently severe pathological condition. The awareness of GPs and the general population should be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
146
3
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 10 publications
8
146
3
4
Order By: Relevance
“…For example, a French primary care study of the prevalence, recognition and treatment of social phobia found that detection rates were increased in the presence of comorbid depression (66%, compared with 53% in those without depression) [I] (Weiller et al, 1996). However the presence of a seemingly more pressing comorbid condition can result in sub-optimal treatment for the anxiety disorder.…”
Section: Recommendations: Increased Awareness Of Anxiety Disordersmentioning
confidence: 99%
“…For example, a French primary care study of the prevalence, recognition and treatment of social phobia found that detection rates were increased in the presence of comorbid depression (66%, compared with 53% in those without depression) [I] (Weiller et al, 1996). However the presence of a seemingly more pressing comorbid condition can result in sub-optimal treatment for the anxiety disorder.…”
Section: Recommendations: Increased Awareness Of Anxiety Disordersmentioning
confidence: 99%
“…Prema istraživanjima, učestalost socijalnog anksioznog poremećaja kreće se između 13,3% u SAD [10] i 14,4% u Evropi [11].…”
Section: Diskusijaunclassified
“…More than 80% of people who suffer from social phobia have another comorbid disorder (14,15). This disorder causes more pervasive problems than other anxiety disorders (15)(16)(17)(18). Retrospective and prospective epidemiological studies suggest that social phobia can create confusion and deep problems in life, including problems in school and college achievement (2,11,18) and can disrupt job performance (15,16) and social development (2,15,16).…”
Section: Introductionmentioning
confidence: 99%